Detection of Anti- Ovarian Antibodies and Anti-sperm Antibodies in Sera of Sub Fertile Women in Baghdad - Farhan A Risan (Journal of Global Pharma Technology, 2018)
The study was carried out through the period March/2017 to October/2017,for estimate the ant ovarian antibodies and anti sperm antibodies in sera (fifty nine) sub fertile women compared with( twenty seven ) healthy women as control group. Their mean aged 28 years. The diagnosis of anti ovarian antibodies concentration were a done by enzyme linkage immunosorbent assay(ELISA) A high significant in cement (p≤ 0.001 ) was observed in the sera of sub fertile women( 819 uL) compared with control group( 476uL),while the anti-sperm antibodies concentration show high significant in cement (p≤ 0.0l) in the sera of sub fertile women(211 uL) compared with control group(42 UL).Keywords: Anti-ovarian antibodies, Anti-sperm antibodies, Sub fertile women.